On Aliovalent Substitution on the Li Site in LiMPO4: an X‐ray Diffraction Study of the Systems LiMPO4–M1.5PO4 (= LixM1.5–x/2PO4; M = Ni, Co, Fe, Mn). Issue 1 (15th October 2013) - Clemens, Oliver; Haberkorn, Robert; Springborg, Michael; Beck, Horst Philipp
Abstract In this paper we report on the possibility of Li substitution by M2+ to various high degrees in LiMPO4 olivine‐type compounds (M = Ni, Co, Fe, Mn), depending on the kind of transition metal M. The experimental studies were carried through by reacting stoichiometric amounts of LiMIIPO4 and MII1.5PO4 (= MII3(PO4)2) to form compounds of composition LixMII1.5–x/2PO4 (0 ≤ x ≤ 1). A complete solid solution over the whole range of x was found for M = Ni (together with a second order structural transition from orthorhombic to monoclinic for decreasing x), whereas far smaller degrees of dopability of the Li site were found for LiCoPO4 and LiFePO4 (up to compositions of approx. (Li0.8Co0.1)CoPO4 and approx. (Li0.9Fe0.05)FeO4. In addition, the nearly stoichiometric monoclinically distorted olivine‐type compounds with compositions (Li0.42–0.47Co0.29–0.265)CoPO4 and (Li0.14–0.16Fe0.43–0.42)FePO4 could be identified and are described in this article.